Quality of life in patients with AMD after laser stimulation of the retina with subsequent nutrient supplementation (Ukrainian Journal of Ophthalmology, 2026)
Background: Previous studies of the psychological component of the quality of life (QoL) in patients with age-related maculopathy (ARM) and macular degeneration (AMD) have found that these patients were more likely to show signs of depression compared to older adults with good vision, which, along with their poor visual function, substantially worsened their QoL.Purpose: To investigate the benefits of laser stimulation of the retina with subsequent 6-month daily nutrient supplementation for QoL in patients with ARM and AMD.Materials and Methods: The study involved 34 patients (42 eyes; 16 (47%) male and 18 (53%) female; age, 47 years to 76 years) with ARM and dry AMD. Most of the patients were younger than 65 years. All study eyes received 10 every-day sessions of diode laser stimulation of the retina (LSR) (wavelength, 650 nm; irradiance, mW/cm2; treatment timing, 300 s). Thereafter, patients were administered one capsule of Nutrof® Total daily for 6 months. They completed the 25-item version of the National Eye Institute Visual Function Questionnaire (NEI VFQ-25) and Hospital Anxiety and Depression Scale (HADS) at baseline, immediately after a course of LSR, and after a subsequent 6-month course of nutrient supplementation.Results: In 30 patients (88%), the mean percentage increase in visual acuity was 33.3% after a 6-month course of nutrient supplementation. The HADS scores decreased by 18% after a course of LSR (this decrease was significant), and by 21% after a subsequent 6-month supplementation with Nutrof® Total. The overall emotional distress score improved by 43.1% in 29 patients (85.3%) after a 6-month daily nutrient supplementation. There was a statistically significant improvement in NEI VFQ-25 overall composite following treatment (F=117.6; p=0.00001). This score increased to 70.1 immediately after a course of LSR, and to 76.4 after 6 months of supplementation with Nutrof® Total.Conclusions: The comprehensive treatment (a course of laser stimulation of the retina with subsequent oral supplementation with Nutrof® Total) for ARM and dry AMD resulted in improved visual function, decreased anxiety and depression, and substantially improved QoL at the 6-month time-point.
Keywords: age-related macular degeneration; quality of life; laser stimulation of the retina; nutrient supplementation